Infantile diarrhoea: Breast and bottle feeding compared with special reference to their clinical role - Muzief Munir (Indonesian Pediatric Society, 1985)
This study was conducted to evaluate a clinical presentation of diarrhoea in infants under 2 years of age, in relation to their types of feeding. It was found that the duration of diarrhoea in bottle-fed infants was significantly longer than in breast-fed ones. It was 7.2 Â± 0.46 days in bottle-fed, compared to 5.5 Â± 0.17 days in breast-fed infants. The prevalence of acute Otitis media and Rhinopharyngitis in bottle-fed infants under 1 year of age was higher than in breast-fed infants.f!owever,it was not so after 1 year of age.